Endobronchial neurogenic tumor: A combination of traumatic neuroma and neurofibroma. (2017) - Tandon, Amit
Abstract: Traumatic neuromas are uncommon and benign lesions arising from a peripheral nerve injury during surgery. Here we describe a case with histopathologic features of both a traumatic neuroma and neurofibroma in a patient without integumentary physical exam findings nor prior surgical history. A 54 year old male was admitted for surgical debridement of a foot ulcer. During pre-operative evaluation and review of imaging multiple CT scans revealed a stable, 4 mm endobronchial lesion in the left lower lobe. Given history of nicotine abuse, bronchoscopy was performed. Bronchoscopy showed a pearly, polypoid lesion. Histopathological results showed strong positivity for S-100 protein and spindle cell proliferation. Repeat CT chest showed no new lesions in the bronchial tree. The rarity of this case is noted not only by the limited number of bronchial neurogenic tumors, but the combined features in this case of a traumatic neuroma and neurofibroma which has not been described.